House qualities characteristics relationship on house prices - Mohamad @ Masri, Muhamad Hilmi; Nawawi, Abdul Hadi; Mohd Safian, Edie Ezwan; Ahmad Saleh, Ahmad Fawwaz (e-International Publishing House Ltd, 2018)
The research was conducted to measure the characteristics quality of houses in Malaysia. The aim of this research was to produce significant results of the relationship between house qualities and house prices. The methodology used in this research was primarily by AHP and conducting Regression Analysis between the characteristics and house prices. Data collection gathered through a sampling of landed terrace houses in the Klang district was incorporated for this. The results from the research portray significant findings that can help improve quality of life for targeted households.